Versões digitais para jogos matemáticos: invariantes em paridade, congruência modular, frações e pg - Conceição Junior, Renato (2020)
The work consisted in the idealization and implementation in the programming language of Scratch of online digital versions for games with didactic intent in mathematics, as well as the availability of these games on the site scratch.mit.edu, with the objective that primary school teachers use them as an integral part of didactic sequences and also for the use of students as a hobby and challenges. The idealization was supported by the guidelines suggested by the National Common Curriculum Base (BNCC), which encourage the use, creation and development of digital language in the school environment. The games created were tested by high school math teachers who issued opinions, suggestions and criticisms through online forms made available for this purpose. Each of the games had its main theme cited with the highest frequency of all available in its forms, showing to be consistent with the didactic intentions for which they were created.